Reaction of melon genotypes to didymella bryoniae (Fuckel) rehm - Santos, Lucas da S. [UNESP]; Cândido, Willame dos S. [UNESP]; Rabelo, Hudson de O. [UNESP]; Marin, Marcus V. [UNESP]; Gaion, Lucas A. [UNESP]; Gomes, Rafaelle F.; Camargo, Margarete [UNESP]; Braz, Leila T. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2017)
The cultivation of melon (Cucumis melo L.) in greenhouses has contributed to the increased incidence of fungal diseases, particularly gummy stem blight caused by Didymella bryoniae (Fuckel) Rehm. This disease is currently considered the main disease affecting this crop, causing conditions such as water soaked seedlings, and stem and fruit cankers, reducing productivity and fruit quality. Considering the importance of this disease, the aim of this study was to evaluate the reaction of different C. melo genotypes to D. bryoniae. Sixty-eight different melon genotypes were investigated. Two phenotyping assays were performed to investigate the resistance to the disease, following a randomized block design with four replicates. Subsequently, a new assay was conducted to validate the resistance of the genotypes selected in the previous step, using a randomized block design with three replicates. The plants were inoculated using the toothpick method, and resistance was evaluated according to a grading scale. Also, reaction classes and assay groups were used for classifying the resistance level of the genotype. The JAB-11 and JAB-20 strains were susceptible to the pathogen, as well as the commercial hybrids Louis F1 and Fantasy F1. The hits AC-29, C160, Charentais Fom 1, PI 420145, PI 482398 and PI 532830 were resistant to D. bryoniae, and could become an important gene source for the development of resistant cultivars.
Keywords: Acessions; Cucumis melo; Gummy stem blight; Phenotyping